Poly(methyl methacrylate)-silica-calcium phosphate coatings for the protection of Ti6Al4V alloy - Uvida, Mayara Carla [UNESP] (2023)
Poly(methyl methacrylate) (PMMA)-silica coatings modified with calcium phosphates (CaPs) in the form of hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) have been developed to improve the corrosion resistance and bioactivity of Ti6Al4V titanium alloys, applied in medical and dental implants. PMMA-silica hybrids containing 1000 ppm HA or β-TCP were prepared by combining the sol-gel reactions of tetraethylorthosilicate (TEOS) with the radical polymerization of methyl methacrylate (MMA) and 3-methacryloxypropyl trimethoxysilane (MPTS), used as molecular coupling agent. Bi-layer coatings about 15 μm thick, deposited by immersion on Ti6Al4V, are homogeneous, defect-free, and exhibit strong adhesion to the substrate (>14 MPa). The addition of HA and β-TCP led to a slight increase in thermal stability, without affecting the structural integrity of the highly crosslinked PMMA-silica matrix. The greater hydrophilicity and surface roughness of coatings containing HA and β-TCP are associated with the size and chemical composition of CaPs, necessary for effective osteointegration. The modified coatings showed high anti-corrosion efficiency with low-frequency impedance modulus values of up to 73 GΩ cm2, remaining stable after 150 days of exposure to simulated body fluid (SBF) solution. Graphical Abstract: [Figure not available: see fulltext.]